Produção de linguiça frescal utilizando o pó de aipo em substituição ao nitrito e extrato de alecrim como antioxidante - Siqueira, Felipe Segabinazzi (Universidade do Vale do Rio dos Sinos, 2020)
The fresh sausage is a meat product much appreciated in Brazil. The technological challenges of its processing are related to high susceptibilities to oxidation and microbial proliferation. To avoid changes in product quality and microbiological contamination, the use of preservatives and antioxidants is permitted. It is known that these synthetic additives can cause harm to health, as some types of cancer, so the replacement of these compounds with natural extracts, such as celery (Apium graveolens) and rosemary (Rosmarinus officinalis), has been studied. This work aimed to develop and evaluate the shelf life of a fresh sausage with preservatives and natural antioxidants, stored under refrigeration, in which celery was used as a substitute for nitrite and rosemary as an adjuvant in preventing oxidation. Three samples were produced, one using powdered celery and rosemary extract (LA), a sample using sodium nitrite and sodium erythorbate (LN), and another sample, where no type of preservative (LC). During the study of refrigerated shelf life (15 days), the samples obtained similar results for the pH value; LA obtained higher values of residual nitrite compared to LN, indicating that it may have an activity against microbiological contamination for longer. There was an increase in the oxidation of the LC sample, while in the LA and LN samples there was stability, demonstrating that the additives present in their formulations were effective in preventing oxidation. Regarding microbiological contamination, there was an increase in LC and a slight reduction in both LA and LN, a result that confirms that both preservatives used are effective in combating bacterial proliferation. The physical-chemical analyzes indicated that the samples are within the standards recommended by the legislation. The LA and LN samples were more reddish, while the LC sample had a brownish color, due to the formation of metmyoglobin. In the sensory analysis, the LA sample obtained the highest scores for the items texture, flavor and global acceptance, while in appearance, color and aroma there were no significant differences in relation to LN. LA obtained the highest score for the purchase intention. The study showed that celery associated with rosemary extract can be an adequate technological solution to replace artificial additives when used in the production of fresh sausages.
Keywords: Linguiça frescal; Aipo; Extrato de alecrim; Aditivos naturais; Fresh sausage; Celery; Rosemary extract; Natural additives; ACCNPQ::Ciências da Saúde::Nutrição